1998
DOI: 10.1111/1467-8470.00041
|View full text |Cite
|
Sign up to set email alerts
|

The Value of an Ocean View: an Example of Hedonic Property Amenity Valuation

Abstract: This paper presents a method of quantifying variation in quality in an amenity as a component of an hedonic property amenity valuation. The paper considers the residential land amenity of an ocean view, a situation where there is typically substantial variation in the quality of the view between sites. The method is effectively a scoring system based on three sub-characteristics of the ocean view. It is illustrated by application to a coastal housing subdivision in Western Australia. The results provide an est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 4 publications
2
40
0
Order By: Relevance
“…A factor that makes the investigation of property markets particularly cumbersome within Australia is the lack of centralised data on the value, location, number and type of houses sold (Beer and O'Dwyer 2000), This is the reason for the limited studies that use housing prices to estimate values of non-market goods or services in Australia, Exceptions include Abelson (1997), who compared house prices in Sydney suburbs from the 1970s to 1990s, and Fraser and Spencer (1998) who applied the hedonic price method to a small sample of new house blocks in the same area on Western Australia'S coast. Most of the hedonic pricing studies have used the actual sale price of the property and hence have directly followed the property market, A few studies have used vacant land sales, e.g, Fraser and Spencer (1998) and Rinehart and Pompe (1999).…”
Section: 1 Unimproved Property Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A factor that makes the investigation of property markets particularly cumbersome within Australia is the lack of centralised data on the value, location, number and type of houses sold (Beer and O'Dwyer 2000), This is the reason for the limited studies that use housing prices to estimate values of non-market goods or services in Australia, Exceptions include Abelson (1997), who compared house prices in Sydney suburbs from the 1970s to 1990s, and Fraser and Spencer (1998) who applied the hedonic price method to a small sample of new house blocks in the same area on Western Australia'S coast. Most of the hedonic pricing studies have used the actual sale price of the property and hence have directly followed the property market, A few studies have used vacant land sales, e.g, Fraser and Spencer (1998) and Rinehart and Pompe (1999).…”
Section: 1 Unimproved Property Valuesmentioning
confidence: 99%
“…Most of the hedonic pricing studies have used the actual sale price of the property and hence have directly followed the property market, A few studies have used vacant land sales, e.g, Fraser and Spencer (1998) and Rinehart and Pompe (1999). Rinehart and Pompe (1999, p. 58) In relation to improved land -the capital sum which the fee simple of the land might be expected to realise ifoffered for sale on such reasonable terms and conditions as a bona fide seller would require, assuming that, at the time as at which the value is required to be ascertained for the purposes of this Act, the improvement did not exist.…”
Section: 1 Unimproved Property Valuesmentioning
confidence: 99%
“…30852 for earlier period (-1993); 33642 for latter period (-1994), i.e. FIM 31,000 (25%) and 34,000 (19%); shore proximity dummy insignificant For the three price segments: the higher the price group, the share of observations possessing a shore view is not significantly larger Hedonic study, value of a river view, dummy variable, house sales Price premium 28% Fraser & Spencer (1998), western Australia Hedonic study, ocean view for undeveloped residential sites (n=114), scoring matrix 0-10 based on the potential loss of view and degree Linear, logarithmic The best ocean view increased the price 25%; a better view increased the price, but with a diminishing rate (marginal utility) ; elevation not reported, distance not significant (Rsq.adj. :0.79)…”
Section: Neural Network Approachmentioning
confidence: 97%
“…Furthermore, they found that the value of an ocean view rose in the late 80s, during a period of market upswing. Fraser and Spencer (1998) found out that the best ocean view increased the price 25%; a better view increased the price, but with a diminishing rate (marginal utility).…”
Section: Viewmentioning
confidence: 97%
“…Fraser and Spencer [2] considered the residential land amenity of an ocean view by a scoring system based on three sub-characteristics of the view based on housing data from 114 sites in Western Australia. The three dimensions they used are degree of panorama, potential loss of view and elevation.…”
Section: Values Of Coastal Landscapes For Owners or Occupiers Of Propmentioning
confidence: 99%